An assessment of the land use and land cover changes in Shurugwi district, Midlands Province, Zimbabwe. - Matsa, Mark; Muringaniza, K. (2016)
Zimbabwe’s fast-track land reform programme and other economic activities have caused considerable land cover /land use changes to the country’s ecological environment and Shurugwi district has been no exception. Most of these changes are yet to be captured and documented as essential baseline information for developmental purposes. This paper seeks to establish the current status of land use and land cover changes for Shurugwi district as well as to determine the extent of these changes using Geographic Information System and remote sensing techniques. Three satellite images for three different years (1991, 2000 and 2009) were used to come up with a land use/land cover map classification for Shurugwi district. Image processing and image classification were done in order to establish the land use /land cover of the district. To determine the extent of land use/land cover changes in the district between 1990 and 2009 Landsat images of the district were downloaded from the Global Land cover Facility as well as from Google Earth Image Domain. The images were analysed using change detection techniques along with Google Earth screen to screen images to come up with the extent of the changes that have occurred. Results show that cultivation and bare land dominate land use/land cover for the district at 53.4% while degraded land covers 26.6% with the rest shared between vegetation (18.1%) and water (2%). There has been considerable land use/land cover change in Shurugwi district between 1990 and 2009.The greatest change occurred to vegetation which experienced a 9.4% decrease between 1991 and 2000 and an even higher decrease of 11.6% between 2000 and 2009.The study recommends that government concludes its land reform and resettlement programme to reduce continued ecological destruction. The Environmental Management Agency should also educate newly resettled farmers and other stakeholders like miners (including gold panners) on the need for proper environmental management essential for sustainable development.